219k views
2 votes
3(5f + 2)- f = 2(-3)

pls help asap

2 Answers

5 votes

Answer:

14f =-12

Explanation:

3×5f+ 3×2-f = 2×-3

15f - f + 6 = -6

14f= -6

User Zachary Dale
by
5.5k points
5 votes

Answer: -6/7

Explanation:

3(5f+2)-f=2(-3)

15f+6-f=-6 ⇔ distributive property

14f+6=-6 ⇔ subtract f from 15f

14f=-12 ⇔ subtraction property of equality (subtract 6 on both sides)

f=-12/14 ⇔ division

f=-6/7

Hope this helps!! :)

Please let me know if you have any question or need further explanation

User Charlie Fish
by
5.1k points